Azide Passivation of Black Phosphorus Nanosheets: Covalent Functionalization Affords Ambient Stability Enhancement. (2nd January 2019) - Liu, Yajuan; Gao, Pengfei; Zhang, Taiming; Zhu, Xianjun; Zhang, Mengmeng; Chen, Muqing; Du, Pingwu; Wang, Guan‐Wu; Ji, Hengxing; Yang, Jinlong; Yang, Shangfeng
Abstract: Two‐dimensional (2D) black phosphorus (BP) has a unique band structure, but it suffers from low ambient stability owing to its high reactivity to oxygen. Covalent functionalization has been demonstrated to passivate the reactive BP effectively, however the reported covalent functionalization methods are quite limited to aryl diazonium and nucleophilic additions affording P−C and P−O−C single bonds, for which the retaining of one unpaired electron in the Group 15 phosphorus atom hampers the passivation effect. Now, covalent azide functionalization of BP nanosheets (BPNSs) is reported, leading to significant enhancement of the ambient stability of BP as confirmed by UV/Vis spectroscopic studies. The most stable configuration of the azide functionalized BPNSs (f‐BPNSs) is predicted by theoretical calculations, featuring the grafting of benzoic acid moiety onto BPNSs via the unprecedented P=N double bonds formed through in situ nitrene as a reactive intermediate.